Implementation of Communication and Maqāṣid al-Sharī‘ah in Increasing Economic Independence to Prevent Stunting - Nur Saniah; Marlina Marlina; Ade Khadijatul Z. Hrp; Rahmat Rahmat (Bulletin of Indonesian Islamic Studies, 2025)
This study aims to analyze the contribution of communication and the principles of Islamic law (maqāṣid al-sharī‘ah) in efforts to increase community economic independence, identify factors that influence multisectoral communication in stunting prevention, and explore the relationship between economic independence and stunting prevention. The locus of this research is Mandailing Natal Regency and Padangsidimpuan City, two areas in North Sumatra with high stunting rates. Maqāṣid al-sharī‘ah, which emphasizes the protection of religion, life, mind, descendants, and property, can provide a new approach to reducing stunting through increasing economic independence. A qualitative approach was used in this study, using the Focus Group Discussion (FGD) method to explore the views of the community and stakeholders. Increased economic independence contributes significantly to improving the nutritional status and health of children. Economic independence allows better access to nutritious food and health services, and increases parental knowledge about nutrition. Economic empowerment programs that focus on women can improve their social and economic status, which has a positive impact on childcare. Furthermore, greater economic independence improves families' ability to pay for health services and invest in children's education. The results of the study indicate that the synergy between communication activities and emphasizing the values ​​of Islamic law (maqāṣid al-sharī‘ah) in efforts to increase economic independence can contribute to reducing stunting rates. The application of communication principles and the maqāṣid al-sharī‘ah (Islamic principles) in economic empowerment programs focuses not only on stunting reduction but also on improving overall community welfare. Therefore, this research is expected to provide new insights into the importance of a holistic approach to stunting prevention that involves various sectors and sharia values.